2020
DOI: 10.1002/pol.20190082
|View full text |Cite
|
Sign up to set email alerts
|

Redox polymers incorporating pendant 6‐oxoverdazyl and nitronyl nitroxide radicals

Abstract: Polymers comprised of redox-active organic radicals have emerged as promising materials for use in a variety of organic electronics, including fast-charging batteries. Despite these advances, relatively little attention has been focused on the diversification of the families of radicals that are commonly incorporated into polymer frameworks, with most radical polymers being comprised of nitroxide radicals. Here, we report two new examples prepared via ring-opening methathesis polymerization containing 6-oxover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Whereas highly different first reduction potentials were observed for the five NN biradicals, covering a range of more than 370 mV, the first oxidation potentials of the nitronyl nitroxides are very similar (Table S2). As oxidation potentials between 330 and 520 mV are typically observed for NNs in literature, the first oxidation process can be ascribed to the formation of an oxammonium cation from the respective (bi)­radical. ,,,,,, This is further corroborated by analogous CV and DPV studies of the silylated precursors (Figures S29 and S30 and Table S1), which reveal a similar redox behavior as observed for the respective nitronyl nitroxides, but the pronounced oxidation event at 366–422 mV (all potentials vs Fc 0/+ ), being observed for all NN, is absent in PBI–Si, IIn–Si, and PhDPP–Si. Electron-rich ThDPP–Si and FuDPP–Si exhibit an additional oxidation process between 300 and 400 mV (Figure S30), which can be ascribed to the DPP chromophore oxidation, although these processes occur at slightly higher potentials (500 mV) in the unsubstituted parent chromophore due to the smaller π-system.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Whereas highly different first reduction potentials were observed for the five NN biradicals, covering a range of more than 370 mV, the first oxidation potentials of the nitronyl nitroxides are very similar (Table S2). As oxidation potentials between 330 and 520 mV are typically observed for NNs in literature, the first oxidation process can be ascribed to the formation of an oxammonium cation from the respective (bi)­radical. ,,,,,, This is further corroborated by analogous CV and DPV studies of the silylated precursors (Figures S29 and S30 and Table S1), which reveal a similar redox behavior as observed for the respective nitronyl nitroxides, but the pronounced oxidation event at 366–422 mV (all potentials vs Fc 0/+ ), being observed for all NN, is absent in PBI–Si, IIn–Si, and PhDPP–Si. Electron-rich ThDPP–Si and FuDPP–Si exhibit an additional oxidation process between 300 and 400 mV (Figure S30), which can be ascribed to the DPP chromophore oxidation, although these processes occur at slightly higher potentials (500 mV) in the unsubstituted parent chromophore due to the smaller π-system.…”
Section: Resultssupporting
confidence: 80%
“…In contrast to the oxidation process, reduction potentials of NNs are hardly reported in literature and are thus much less indicative. For instance, reduction potentials between −1270 and −1330 mV have been reported for NN-containing redox polymers or fused thiophene systems, , however, these reduction potentials strongly depend on the π-system. Accordingly, it can be concluded that the electron accepting properties (reduction) are strongly driven by the chromophore core and reflect its electron affinity, whereas the first oxidation potential is determined by the nitronyl nitroxide radical moiety.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The excellent smoothness of the deposits demonstrated in Figure 1e is also consistent with the very low roughness and high uniformity exhibited by 6-oxoverdazyl polyradicals synthesized by wet chemistry. 6,32 Matrix-assisted laser desorption and ionization (MALDI) mass spectrometry was used to confirm the Grubbs-III-assisted surface polymerization of N-6OV to produce a PN-6OV. MALDI is an effective tool for the detection of polymers in deposits with minimal fragmentation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%